Consistent benefits of fungicide reduction on arthropod predators and predation rates in viticulture: a five-year experiment - Jo Marie Reiff; Theresa Pennington; Sebastian Kolb; Konrad Theiss; Ekaterina Alakina; Marvin Ehringer; Paul Mason; Rosalie Shrestha; Martin H. Entling; Christoph Hoffmann (BioControl, 2023)
For reliable pest suppression, benefits of habitat management for natural enemies of agricultural pests need to be consistent over time. Unfortunately, most research projects allow only for one or two years of data collection. Here, we present a five-year study on effects of fungicide reduction and altered plant architecture on arthropod abundances and natural pest control in an experimental vineyard. The vineyard rows were divided into eight groups, half of which were trained in vertical shoot position (“trellis system”) and the other half as semi-minimal pruned hedge (“minimal pruning”). Every row was divided in three sections receiving three different plant protection intensities, respectively, with fungicides certified for organic viticulture. In each year we sampled arthropods from the grapevine canopy by standardized leaf collection and beat-sheet sampling, and exposed baits of a major grapevine pest ( Lobesia botrana ) to assess natural pest control. Arthropods, in particular predators, benefited from reduced fungicide sprayings and in turn promoted natural pest control. In contrast, effects of minimal pruning were less strong, and restricted to the leaf mesofauna, earwigs and leafhoppers. Across the five study years with their variable weather conditions, we conclude that the advantages of reduced fungicide sprayings in fungus-resistant varieties are consistent over time.